Erratum: Corrigendum to “serum thiamine concentration and oxidative stress as predictors of mortality in patients with septic shock” (Journal of Critical Care (2014) 29(2) (249–252) (S0883944113004723) (10.1016/j.jcrc.2013.12.004)) - Costa, Nara Aline [UNESP]; Gut, Ana Lúcia [UNESP]; de Souza Dorna, Mariana [UNESP]; Pimentel, José Alexandre Coelho; Cozzolino, Silvia Maria Franciscato; Azevedo, Paula Schmidt [UNESP]; Fernandes, Ana Angélica Henrique [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; de Paiva, Sergio Alberto Rupp [UNESP]; Minicucci, Marcos Ferreira [UNESP] (Elsevier, 2016)
The authors reviewed the data and regret that the results of protein carbonyl in Table 1 are inverted. However, the discussion and conclusion are correct. The correct form is inserted below: The authors would like to apologize for any inconvenience caused.